Impact of ulcerative colitis on liver‐related outcomes of children with primary sclerosing cholangitis. (4th April 2022) - Sathiaseelan, Mohana; Bolia, Rishi; Barallon, Raychel; Alex, George; Hardikar, Winita; Rajanayagam, Jeremy
Abstract : Aim: Primary sclerosing cholangitis (PSC) is a chronic progressive cholestatic disorder associated with ulcerative colitis (UC). Although the inflammatory bowel disease phenotype has been characterised in patients with PSC, the impact of UC on the course and progression of PSC‐UC is less clear. We aimed to evaluate the effects of UC on liver‐related outcomes in children with PSC. Methods: Retrospective analysis of children aged ≤18 years diagnosed with PSC with/without UC at a single tertiary paediatric liver unit between January 1998 and May 2016. Patients were followed up until transition to an adult service. Outcomes studied included biliary complications, clinically significant portal hypertension, need for liver transplantation and post‐transplantation recurrence. Results: Fifty‐one children (31 female) were diagnosed with PSC (median age – 11.3 years (interquartile range 7)), follow‐up median duration 54 months (interquartile range 56). Thirty‐seven (73%) patients had concurrent UC, of which 26 had their diagnosis confirmed prior to or within 6 months of PSC diagnosis (early‐onset). PSC complications were more common in children with PSC‐UC compared with PSC alone (24/37 (65%) vs. 2/14 (14%); P = 0.001). Furthermore, children with endoscopically mild or moderate UC at diagnosis showed a greater propensity for liver‐related complications compared with children with severe UC (24/32 vs. 0/5; P = 0.003). Children with late‐onset UC had higher rates of clinically significant portal hypertension (5/11 (45%) vs. 3/26 (12%); P = 0.007) and liver transplantation (5/11(45%) vs. 2/26 (8%); P = 0.02). Children with PSC‐UC had significantly higher rates of pancolitis, rectal sparing and milder colitis than those with UC alone. Conclusion: The presence and a later‐onset of UC are associated with more significant progression to end‐stage liver disease. There is an inverse trend between UC severity and PSC severity in children with concurrent PSC‐UC.